2021
DOI: 10.2147/jhc.s292139
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hepatocellular Carcinoma Risk in Patients with Chronic HCV Infection and a Sustained Virological Response to Direct-Acting Antivirals

Abstract: Chronic infection with hepatitis C virus (HCV) may complicate with hepatocellular carcinoma (HCC), especially in patients with cirrhosis. Although the achievement of a sustained virological response (SVR) had been associated with a reduction in the risk of HCC already in the Interferon era, some concerns initially raised following the use of direct-acting antivirals (DAA), as their use was associated with increased risk of HCC development and aggressiveness. However, studies demonstrated that the risk of HCC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…However, given the high heterogeneity of HCC, a more personalized surveillance strategy based on individual risk assessment is an unmet need. Promising results have been obtained from non-invasive scoring systems (NSS) combining demographic, clinical, and biochemical variables normally collected during standard clinical practice [11,12]. Due to their cost-effectiveness, this approach could be suitable for the surveillance of patients at risk of HCC development.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the high heterogeneity of HCC, a more personalized surveillance strategy based on individual risk assessment is an unmet need. Promising results have been obtained from non-invasive scoring systems (NSS) combining demographic, clinical, and biochemical variables normally collected during standard clinical practice [11,12]. Due to their cost-effectiveness, this approach could be suitable for the surveillance of patients at risk of HCC development.…”
Section: Introductionmentioning
confidence: 99%
“…The former finding is in line with previous studies that reported portal hypertension being associated with post‐SVR HCC. [ 5 ] Conversely, diabetes was not an independent predictor of HCC in this meta‐analysis, whereas other metabolic factors were not evaluated. The role of metabolic disorders on post‐treatment HCC risk probably needs additional investigations for several reasons.…”
mentioning
confidence: 79%
“…[ 3 ] The wide use of DAAs to cure large cohorts of patients with advanced liver disease and/or comorbidities, who were previously contraindicated to IFN‐based therapies, has recently livened up the debate on long‐term surveillance strategies and their cost‐effectiveness. Although the risk of hepatic decompensation remains low, also in patients with severe portal hypertension, before treatment, [ 1,4 ] the residual annual risk of de novo HCC has been estimated to be 2.0%–2.5% in SVR persons with cirrhosis following DAAs, [ 5 ] thus further supporting the need for post‐treatment surveillance in this subgroup of patients. Conversely, data on the residual risk of HCC in patients with F3 fibrosis are controversial, as long as recommendations from scientific societies are not univocal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of hepatocellular carcinoma in chronic hepatitis C patients with significant or advanced fibrosis or cirrhosis may occur after resolution of HCV infection 28 . The tumour is believed to arise from hepatic areas of residual scar 29 . In this scenario, new curative oral HCV antivirals ameliorate but do not halt the risk of liver cancer in chronic hepatitis C patients 30 .…”
Section: Discussionmentioning
confidence: 99%